Enterprise Resource Planning systems selection, application, and implementation on the example of Simple.ERP software package - Zarzycki, Hubert (Wybór, zastosowanie i wdrażanie systemów ERP na przykładzie pakietu oprogramowania Simple.ERP, 2011)
This paper presents an overview of the most important tasks of ERP and MRP systems. Notes of ERP package selection methodology of a software customized for specific use of companies are presented. Functionality comparison and analysis of a few exemplary software systems for management and resource planning of enterprise was conducted. Among the analyzed systems, Simple ERP package was selected as an application well suited to the needs of domestic consumers. Afterwards, the general concepts of ERP software and the most important modules and related areas of a company’s activities were explained based on solutions provided by Simple inc. The author advocates increased use of innovative technologies and modern information systems in the data processing activities in order to provide comprehensive support of a company’s management
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 281-291
Keywords: ERP; MRP; Simple.ERP; information systems; ERP implementation